. - Paternotte, David (Nomadías, 2009)
This article investigates the relationship between same-sex marriage and access to citizenship. If we agree that homosexuals have been a historically minorized social group, the demand for same-sex marriage reveals a paradox that must be questioned: the institution which was considered as one of the cornerstones of oppression has become worth struggling for. It is also regarded as a potential way to citizenship. This piece of writing attempts to further define the inclusion model which could underpin this claim. Given the limits of existing analytical models, it suggests a new one, which is called inclusion through resignification, and is inspired by the work of Judith Butler. Through its confrontation to other examples, this model appears as intrinsically fragile, a characteristic linked to its perpetual openness.